Method for producing polyolefin resin foam particles and polyolefin resin foam particles
Patent Information
- Application Number
- JP2025262086
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2025-03-31
- Filing Date
- 2025-12-17
- Publication Date
- 2026-10-14
AI Technical Summary
【0009】 本発明のポリオレフィン系樹脂発泡粒子の製造方法は、気泡核剤としてタルクを使用するにも関わらず高発泡倍率のポリオレフィン系樹脂発泡粒子を製造することができる。
Smart Images

Figure 2026167433000003 
Figure 2026167433000001 
Figure 2026167433000002
Abstract
Description
[Technical Field]
[0001] This invention relates to a method for producing polyolefin resin foam particles and to polyolefin resin foam particles. [Background technology]
[0002] Conventionally, when manufacturing foamed polyolefin resin particles, it is a known technique to typically add a bubble nucleating agent.
[0003] For example, Patent Document 1 discloses a manufacturing method for producing polyolefin resin foam particles using an inorganic blowing agent such as carbon dioxide, and resin particles containing a polyolefin resin and a water-containing inorganic compound. Talc is given as an example of the water-containing inorganic compound, and it is disclosed that compounds such as talc that are insoluble or sparingly soluble in water are preferable for exhibiting the effect of a bubble nucleating agent. [Prior art documents] [Patent Documents]
[0004] [Patent Document 1] Japanese Patent Publication No. 2009-215485 [Overview of the project] [Problems that the invention aims to solve]
[0005] When talc is included as a bubble nucleating agent and carbon dioxide is used as a blowing agent, the ability of carbon dioxide to impregnate polyolefin resins tends to be very low. Therefore, although it is possible to produce resin particles using polyolefin resin and talc as disclosed in Patent Document 1 and then foam them to obtain foamed polyolefin resin particles, it was difficult to obtain a sufficient foaming ratio in this case.
[0006] The present invention has been made in view of the above-mentioned problems, and provides a method for producing polyolefin resin foam particles that can achieve a high foaming ratio, and polyolefin resin foam particles. [Means for Solving the Problems]
[0007] The method for producing polyolefin-based resin expanded particles of the present invention is a method for producing polyolefin-based resin expanded particles by discharging polyolefin-based resin particles containing carbon dioxide, which are dispersed in an aqueous medium in a closed vessel, from the inside of the closed vessel to a pressure lower than the pressure inside the closed vessel to expand the polyolefin-based resin particles, wherein the polyolefin-based resin particles are characterized by containing ammonium nitrate and talc.
[0008] The polyolefin-based resin expanded particles of the present invention are characterized in that the average cell diameter of the polyolefin-based resin expanded particles is 20 μm or more and 250 μm or less, and the polyolefin-based resin expanded particles contain ammonium nitrate and talc. [Effects of the Invention]
[0009] The method for producing polyolefin-based resin expanded particles of the present invention can produce polyolefin-based resin expanded particles with a high expansion ratio even though talc is used as a cell nucleating agent. [Brief Description of the Drawings]
[0010] [Figure 1] This is a photograph of a cut surface formed by cutting the expanded particles of Comparative Example 2 into approximately two equal parts. [Modes for Carrying Out the Invention]
[0011] First, the outline of the present invention will be described below. In the following, the method for producing polyolefin-based resin expanded particles of the present invention may be referred to as the production method of the present invention. The production method of the present invention is a method for producing polyolefin-based resin expanded particles by discharging polyolefin-based resin particles containing carbon dioxide, which are dispersed in an aqueous medium in a closed vessel, from the inside of the closed vessel to a pressure lower than the pressure inside the closed vessel to expand the polyolefin-based resin particles. In the manufacturing method of the present invention, polyolefin resin particles to which ammonium nitrate and talc have been added are used. According to the manufacturing method of the present invention having the above configuration, by using talc as a bubble nucleating agent and ammonium nitrate, it is possible to produce foamed particles with a high foaming ratio. Of course, it is also possible to produce polyolefin resin foamed particles with an appropriately suppressed foaming ratio using the manufacturing method of the present invention, and it is possible to provide a molded polyolefin resin foamed particle article using such a product. Further details of the present invention will be described below. Note that, in relation to the number of carbon atoms in the present invention, the notation "Y (number) ~ X (number)" can be interpreted as "Y or greater and X or less". Furthermore, in the following description, preferred numerical ranges of the present invention may be indicated as appropriate. In this case, preferred ranges, more preferred ranges, and particularly preferred ranges regarding the upper and lower limits of the numerical range can be determined from all combinations of the upper and lower limits.
[0012] <Polyolefin resin particles> The polyolefin resin particles used in the manufacturing method of the present invention contain a polyolefin resin, talc, and ammonium nitrate. The polyolefin resin particles consist of polyolefin resin at a concentration of 50% or more by mass of 100% by mass of the resin constituting the resin particles, and other resins other than polyolefin resin may be mixed in as appropriate. As the polyolefin resin, for example, polyethylene resins, polypropylene resins, polybutene, polypentene, and copolymers of olefin monomers and other monomers can be used. The polyolefin resin is preferably one or more selected from polyethylene resins and polypropylene resins, and more preferably a polypropylene resin. In relation to the present invention, the resin that is added in the largest amount, making up 50% by mass or more of the total resin constituting the resin particles, is called the base resin. That is, in the present invention, a polyolefin resin is the base resin. The amount of the polyolefin resin in the total resin constituting the resin particles is preferably 80% by mass or more, more preferably 90% by mass or more, even more preferably 95% by mass or more, and particularly preferably 100% by mass. Furthermore, the resin constituting the polyolefin resin particles is preferably 85% by mass or more, more preferably 90% by mass or more, and even more preferably 95% by mass or more, based on 100% by mass of the polyolefin resin particles. On the other hand, the upper limit of the amount of resin added per 100% by mass of the polyolefin resin particles can be determined by considering the amount of talc and ammonium nitrate added to the polyolefin resin particles.
[0013] [Polypropylene resin] The polypropylene-based resin, which is the base resin, refers to a propylene copolymer containing 50% by mass or more of propylene homopolymers and / or structural units derived from propylene. Examples of the propylene homopolymers include isotactic polypropylene, syndiotactic polypropylene, and atactic polypropylene. These resins, as exemplified as propylene homopolymers, may be used individually or as a mixture of two or more. The propylene copolymer preferably contains 80% by mass or more, and more preferably 90% by mass or more, structural units derived from propylene in the polypropylene resin. The content of structural units derived from propylene in the propylene copolymer is preferably 99% by mass or less, and more preferably 98% by mass or less. Examples of such propylene copolymers include copolymers of propylene and ethylene and / or α-olefins having 4 to 20 carbon atoms. Examples of the α-olefins include 1-butene, 1-pentene, 1-hexene, 1-octene, and 4-methyl-1-butene. Other examples of propylene copolymers include ethylene-propylene random copolymers, propylene-butene random copolymers, and ethylene-propylene-butene random copolymers. These propylene copolymers may be, for example, random copolymers or block copolymers, but random copolymers are preferred. Examples of the propylene copolymer include impact-resistant polypropylene (block polypropylene) composed of two or more phases, including a continuous phase of propylene polymer and a rubber phase dispersed within that continuous phase. An example of a material constituting the rubber phase is ethylene-α-olefin copolymer. These resins, exemplified as propylene copolymers, may be used individually or as a mixture of two or more. Furthermore, the polypropylene resin may be a linear polypropylene resin, a branched polypropylene resin, or a combination thereof.
[0014] [Polyethylene resin] Examples of polyethylene-based resins used as the base resin include ethylene homopolymers or ethylene copolymers containing more than 50% by mass of structural units derived from ethylene. Specific examples of polyethylene-based resins include low-density polyethylene, high-density polyethylene, linear low-density polyethylene, ultra-low-density polyethylene, ethylene-vinyl acetate copolymers, ethylene-methyl methacrylate copolymers, ethylene-methacrylic acid copolymers, and ionomer resins in which the intermolecules of ethylene-methacrylic acid copolymers are crosslinked with metal ions. When the polyethylene-based resin is a copolymer, the copolymer may be a block copolymer, a random copolymer, or a graft copolymer. Furthermore, the polymer described above may be crosslinked, but it is preferable that it be uncrosslinked.
[0015] The melting point of the polypropylene resin used as the polyolefin resin is preferably 155°C or lower. By using the foamed particles of the present invention made with a polyolefin resin exhibiting the above melting point range, a foamed particle molded article with superior appearance can be molded at a lower molding temperature. From the viewpoint of improving this effect, the melting point of the polyolefin resin is more preferably 150°C or lower, and even more preferably 145°C or lower. On the other hand, from the viewpoint of further improving the heat resistance and mechanical strength of the foamed particle molded article, the melting point of the polyolefin resin is preferably 130°C or higher, more preferably 135°C or higher, and even more preferably 138°C or higher. Furthermore, the melting point of the polyethylene resin used as the polyolefin resin particles is preferably 140°C or lower. By using the foamed particles of the present invention made with a polyolefin resin exhibiting the above melting point range, foamed particles with excellent fusion properties and moldability can be obtained even when molded at low molding temperatures. From the viewpoint of improving this effect, the melting point of the polyolefin resin is more preferably 135°C or lower, and even more preferably 130°C or lower. On the other hand, from the viewpoint of ensuring that the molded article is less prone to shrinkage and deformation after in-mold molding and has excellent recovery properties, the melting point of the polyolefin resin is preferably 110°C or higher, more preferably 115°C or higher, and even more preferably 120°C or higher.
[0016] [Other resins] The resin constituting the polyolefin resin particles may consist solely of the polyolefin resin described above, or it may contain other resins together with the polyolefin resin, to the extent that it does not hinder the purpose and effects of the invention. The other resins used in the resin may be one type or a combination of two or more types. Other resins include, but are not limited to, resins selected from the group consisting of thermoplastic resins other than polyolefin resins and thermoplastic elastomers. In the context of this invention, "other resins" also includes elastomers that can be used in the production of foamed particles, in addition to general resins. Examples of the thermoplastic resins include polystyrene resins, polycarbonate resins, polyvinyl chloride resins, polymethacrylic resins, acrylonitrile resins, polyester resins, polyamide resins, and blends thereof. Examples of the aforementioned thermoplastic elastomers include olefin-based thermoplastic elastomers (TPO) and urethane-based thermoplastic elastomers (TPU).
[0017] The amount of other resins added to 100% by mass of the resin constituting the resin particles is preferably 20% by mass or less, more preferably 10% by mass or less, even more preferably 5% by mass or less, and particularly preferably 0% by mass. In other words, it is particularly preferable that the resin constituting the polyolefin resin particles is substantially composed of only polyolefin resin.
[0018] [talc] In this invention, talc refers to a mineral whose main component is hydrated magnesium silicate (3MgO·4SiO2·H2O).
[0019] For example, as shown in Patent Document 1, it is known that talc is added to polypropylene resin particles as a bubble nucleating agent. However, when carbon dioxide is used as a blowing agent and talc is used as a bubble nucleating agent, it is difficult to achieve a high foaming ratio. The inventors of this invention have therefore diligently investigated this problem. When talc is blended into resin particles, carbon dioxide, as a blowing agent, makes it difficult to increase the foaming ratio of the foamed particles, and attempts to increase the foaming ratio tend to generate excessive bubbles within the foamed particles. The inventors of this invention have found that when carbon dioxide is used as a blowing agent, it is possible to achieve a high foaming ratio by adding ammonium nitrate together with talc.
[0020] From the viewpoint of efficiently increasing the foaming ratio of foamed particles while suppressing the amount of talc added, the amount of talc added is preferably 0.01 parts by mass or more and 0.5 parts by mass or less per 100 parts by mass of resin constituting the polyolefin resin particles, more preferably 0.05 parts by mass or more and 0.4 parts by mass or less, and even more preferably 0.07 parts by mass or more and 0.3 parts by mass or less. In other words, the amount of talc added is preferably 0.01 parts by mass or more, more preferably 0.05 parts by mass or more, and even more preferably 0.07 parts by mass or more, per 100 parts by mass of the resin constituting the polyolefin resin particles. Furthermore, the amount of talc added is preferably 0.5 parts by mass or less, more preferably 0.4 parts by mass or less, and even more preferably 0.3 parts by mass or less, per 100 parts by mass of the resin constituting the polyolefin resin particles. The talc content in the foamed particles can be appropriately calculated from the materials used to manufacture the resin particles used to produce the foamed particles. Alternatively, the talc content in the foamed particles may be directly measured using conventionally known methods.
[0021] [Ammonium nitrate] The polyolefin resin particles in the manufacturing method of the present invention contain ammonium nitrate along with the talc described above. In the manufacturing method of the present invention, it was found that by using talc and ammonium nitrate in combination, polyolefin resin foam particles with low apparent density can be obtained due to the synergistic effect of talc and ammonium nitrate. In the present invention, ammonium nitrate contributes to the high foaming of the foam particles and can therefore be understood as a foaming aid.
[0022] Ammonium nitrate is a crystalline solid at room temperature and can be prepared in granular or powder form. Therefore, it is easy to handle during resin particle production and readily added to other components. Ammonium nitrate is also preferable because it is a non-chlorine compound, eliminating the need to worry about rust formation on metal equipment used in the manufacturing process.
[0023] In the manufacturing method of the present invention, the amount of ammonium nitrate added to the resin constituting the polyolefin resin particles is preferably adjusted to be 0.02 parts by mass or more and 0.6 parts by mass or less per 100 parts by mass of the resin constituting the polyolefin resin particles. From the viewpoint of ensuring a wide range of moldable pressures, easily balancing with the amount of talc added, and facilitating in-mold molding of foamed particle molded bodies with a better appearance, the amount of ammonium nitrate added is more preferably 0.03 parts by mass or more and 0.5 parts by mass or less per 100 parts by mass of the resin constituting the polyolefin resin particles, even more preferably 0.04 parts by mass or more and 0.4 parts by mass or less, and particularly preferably 0.05 parts by mass or more and 0.3 parts by mass or less. The ammonium nitrate content in the resin particles can be determined by the same method as the talc content. In other words, the amount of ammonium nitrate added to the resin constituting the polyolefin resin particles is preferably 0.02 parts by mass or more, more preferably 0.03 parts by mass or more, even more preferably 0.04 parts by mass or more, and particularly preferably 0.05 parts by mass or more, per 100 parts by mass of the resin constituting the polyolefin resin particles. Furthermore, the amount of ammonium nitrate added to the resin constituting the polyolefin resin particles is preferably 0.6 parts by mass or less, more preferably 0.5 parts by mass or less, even more preferably 0.4 parts by mass or less, and particularly preferably 0.3 parts by mass or less, per 100 parts by mass of the resin constituting the polyolefin resin particles.
[0024] [Ratio of talc and ammonium nitrate] In the manufacturing method of the present invention, the ratio of the amount of ammonium nitrate added to the amount of talc added is preferably adjusted to 0.2 or more and 6 or less by mass ratio, more preferably to 0.3 or more and 5 or less, even more preferably to 0.4 or more and 4 or less, and particularly preferably to 0.5 or more and 3 or less. In other words, the ratio of the amount of ammonium nitrate added to the amount of talc added is preferably 0.2 or more by mass, more preferably 0.3 or more, even more preferably 0.4 or more, and particularly preferably 0.5 or more. Furthermore, the ratio of the amount of ammonium nitrate added to the amount of talc added is preferably 6 or less by mass, more preferably 5 or less, even more preferably 4 or less, and particularly preferably 3 or less. When the ratio of ammonium nitrate added to talc added is 0.2 or more by mass, it is easy to achieve a moderately low apparent density, and when the ratio is 6 or less, it is easy to moderately lower the apparent density while suppressing the formation of excessive bubbles. The reason for this is not clear, but it is thought to be due to the interaction between talc, which functions as a bubble nucleating agent, and ammonium nitrate. In this invention, excessive bubbles refer to bubbles that have an area of 5% or more of the area of the cut surface formed by cutting the obtained foamed particles into approximately two equal parts. Furthermore, when the ratio of ammonium nitrate added to talc added satisfies the above range, a wide pressure range is available for molding the foamed particles in a mold, and a foamed particle molded body with excellent appearance can be easily obtained.
[0025] From the viewpoint of efficiently increasing the foaming ratio of foamed particles while suppressing the amount of talc and ammonium nitrate added, the total amount of talc and ammonium nitrate added is preferably 0.03 parts by mass or more and 0.7 parts by mass or less, more preferably 0.04 parts by mass or more and 0.5 parts by mass or less, and even more preferably 0.07 parts by mass or more and 0.4 parts by mass or less, per 100 parts by mass of the resin constituting the polyolefin resin particles. In other words, the total amount of talc and ammonium nitrate added is preferably 0.03 parts by mass or more, more preferably 0.04 parts by mass or more, and even more preferably 0.07 parts by mass or more, per 100 parts by mass of the resin constituting the polyolefin resin particles. Furthermore, the total amount of talc and ammonium nitrate added is preferably 0.7 parts by mass or less, more preferably 0.5 parts by mass or less, and even more preferably 0.4 parts by mass or less, per 100 parts by mass of the resin constituting the polyolefin resin particles.
[0026] [Other additives] In addition to the resin, talc, and ammonium nitrate described above, the polyolefin resin particles may also contain other additives as appropriate. Other additives include, for example, one or more combinations of functional additives such as colorants (exemplified by carbon black), organic compounds for controlling bubbles, antioxidants, antistatic agents, surfactants, heat stabilizers, light stabilizers, UV absorbers, and flame retardants. Some more effective additives are described below.
[0027] Antioxidants: The thermal decomposition temperature of ammonium nitrate is approximately 200°C. On the other hand, depending on the type of resin that makes up the polyolefin resin particles, the extrusion temperature during the extrusion process to produce pellet-shaped resin particles may exceed 200°C. When ammonium nitrate is thermally decomposed by heating during extrusion, bubbles may be generated in the resulting resin particles. The cause of this is not clear, but it is presumed to be due to the generation of gases such as nitrogen and oxygen during the thermal decomposition of ammonium nitrate. When bubbles are generated in the resin particles, it can induce the generation of excessive bubbles in foamed particles and exacerbate variations in bubble diameter. Therefore, it is preferable to have few or no bubbles in the resin particles.
[0028] In contrast, by adding a hindered phenol antioxidant to the polyolefin resin particles, the generation of bubbles in the resulting resin particles can be suppressed even when the extrusion temperature during the extrusion process is set to a temperature exceeding 200°C. To more fully demonstrate this effect of suppressing bubble generation due to thermal decomposition, it is preferable to add the hindered phenol antioxidant in an amount of 0.01 parts by mass to 1 part by mass, more preferably in an amount of 0.05 parts by mass to 0.8 parts by mass, and even more preferably in an amount of 0.1 parts by mass to 0.6 parts by mass, per 100 parts by mass of the resin constituting the polyolefin resin particles. The hindered phenol antioxidant contained in the polyolefin resin particles may be one type or two or more types.
[0029] Examples of the aforementioned hindered phenol antioxidants include Irganox 1010 (pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]) and Irganox 1330 (3,3',3') manufactured by BASF. Examples include ',5,5',5''-hexa-tert-butyl-α,α',α''-(mesitylene-2,4,6-tolyl)tri-p-cresol), Irganox1035 (thiodiethylenebis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]), Irganox1076 (octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate), and Irganox1135 (benzenepropanoic acid, 3,5-bis(1,1-dimethylethyl)-4-hydroxy-C7-C9 branched alkyl ester). Similarly, examples of the aforementioned hindered phenol antioxidants include Sumirizer GA-80 (bis[3-[3-(tert-butyl)-4-hydroxy-5-methylphenyl]propanoic acid]2,4,8,10-tetraoxaspiro[5.5]undecane-3,9-diylbis(2-methylpropane-2,1-diyl)) and Sumirizer WX-R (4,4'-thiobis(6-tert-butyl-m-cresol)), both manufactured by Sumitomo Chemical Co., Ltd. Note that "Irganox" is a registered trademark of BASF Societas Europia, and "Sumirizer" is a registered trademark of Sumitomo Chemical Co., Ltd.
[0030] The thermal decomposition temperature of ammonium nitrate can be measured using thermogravimetry (TG) and differential thermal analysis (DTA). By heating ammonium nitrate in a completely dry state, the thermal decomposition temperature can be determined from the peak temperature of the endothermic reaction when a weight change in TG is observed and a peak due to the endothermic reaction is observed in DTA. The measurement is performed under a nitrogen atmosphere.
[0031] Carbon Black: Black polyolefin resin foam particle molded articles are used in various fields, including the automotive sector. Therefore, it is a preferred embodiment that carbon black is included as an additional additive in the polyolefin resin foam particles. Examples of carbon blacks used in the present invention include gas furnace black, oil furnace black, acetylene black, channel black, roller black, thermal black, and Ketjen black. When producing the polyolefin resin foam particles containing carbon black, the amount of carbon black added is preferably 0.5 parts by mass or more and 5.0 parts by mass or less per 100 parts by mass of the resin constituting the polyolefin resin particles, more preferably 1 part by mass or more and 4.5 parts by mass or less, and even more preferably 1.5 parts by mass or more and 4.0 parts by mass or less. In other words, the amount of carbon black added is preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, and even more preferably 1.5 parts by mass or more, per 100 parts by mass of the resin constituting the polyolefin resin particles. Furthermore, the amount of carbon black added is preferably 5.0 parts by mass or less, more preferably 4.5 parts by mass or less, and even more preferably 4.0 parts by mass or less, per 100 parts by mass of the resin constituting the polyolefin resin particles. This makes it possible to provide black foamed particles that exhibit a high foaming ratio while adding an appropriate amount of carbon black, and that prevent the formation of excessive bubbles.
[0032] When producing the polyolefin resin foam particles containing carbon black, the ratio of the amount of carbon black added to the amount of ammonium nitrate added is preferably 1 to 50 by mass, and more preferably 5 to 40. By adjusting the ratio within this range, it is easy to produce polyolefin resin foam particles that exhibit sufficient blackness while fully solving the problems of the present invention, namely increasing the foaming ratio and suppressing excessive foaming.
[0033] Organic compounds for bubble control: To more effectively solve the problems of the present invention, in addition to ammonium nitrate, an organic compound for adjusting bubbles may be added to the polyolefin resin particles. Examples of the organic compound for bubble adjustment include one or more organic compounds selected from the group consisting of aliphatic carboxylate metal salts having 4 to 20 carbon atoms (where the metal of the aliphatic carboxylate metal salt is an alkali metal or an alkaline earth metal) and aliphatic hydroxycarboxylate metal salts having 4 to 20 carbon atoms (where the metal of the aliphatic hydroxycarboxylate metal salt is an alkali metal or an alkaline earth metal). In particular, it is preferable that the organic compound for bubble adjustment is one or more organic compounds selected from the group consisting of aliphatic carboxylate metal salts having 16 to 20 carbon atoms (where the metal of the aliphatic carboxylate metal salt is an alkali metal or an alkaline earth metal) and aliphatic hydroxycarboxylate metal salts having 16 to 20 carbon atoms (where the metal of the aliphatic hydroxycarboxylate metal salt is an alkali metal or an alkaline earth metal). By adding the organic compound for bubble adjustment, foamed particles with a moderately large bubble diameter and lower apparent density are easily obtained.
[0034] [Method for producing polyolefin resin particles] In the manufacturing method of the present invention, the production of polyolefin resin particles can be carried out by known methods for producing resin particles, except for adding talc and ammonium nitrate to a resin containing polyolefin resin. Specifically, for example, the following method can be used. First, the resin containing the polyolefin resin described above, talc, ammonium nitrate, and other additives added as needed are supplied to an extruder and melt-kneaded to obtain a molten mixture. Then, the molten mixture is extruded in strand form from a strand-forming die attached to the downstream side of the extruder at an appropriate extrusion temperature, and the extruded strands are water-cooled and cut with a device exemplified by a pelletizer. In this way, pellet-shaped resin particles containing polyolefin resin, talc, and ammonium nitrate can be obtained.
[0035] The method for incorporating talc and ammonium nitrate into polyolefin resin particles is not limited to the method described above. However, from the viewpoint of incorporating talc and ammonium nitrate into polyolefin resin particles with as little bias as possible, the method of preparing a molten mixture by kneading a resin containing polyolefin resin, talc, and ammonium nitrate using an extruder, as described above, is preferred. Furthermore, from the viewpoint of incorporating talc and ammonium nitrate into polyolefin resin particles with as little bias as possible while suppressing the thermal decomposition of ammonium nitrate, it is preferable to adjust the maximum temperature when molten mixing in the extruder to about 200°C, and / or to add the hindered phenol antioxidant described above. Moreover, from the viewpoint of stably producing foamed particles with a high foaming ratio and suppressed generation of excessive bubbles in the foamed particles, it is preferable to prepare a mixture of talc and ammonium nitrate in advance during the resin particle production process, and to supply the mixture and the resin to the extruder and mix them in the extruder. From a similar viewpoint, it is also preferable to prepare a masterbatch containing the talc, ammonium nitrate, and resin in the process of producing resin particles, and to supply the masterbatch to the extruder.
[0036] <Foaming Process> The manufacturing method of the present invention produces polyolefin resin foam particles by carrying out a foaming process that foams the polyolefin resin particles described above. The foaming process involves releasing polyolefin resin particles containing carbon dioxide, which are dispersed in an aqueous medium within a sealed container, from the sealed container under a pressure lower than the pressure inside the container to cause foaming, thereby producing foamed polyolefin resin particles. A more specific example of the foaming process described above is explained below.
[0037] First, resin particles are dispersed in a sealed container containing an aqueous medium, such as water, and an inorganic dispersant, such as a sparingly soluble inorganic salt or clay mineral, or a dispersion aid, such as a surfactant. Next, a foaming agent is added to the sealed container to impregnate the resin particles with the foaming agent. Then, the resin particles containing the foaming agent and the aqueous medium are released together from the sealed container into an atmosphere with a pressure lower than the pressure inside the sealed container, causing the resin particles to foam. From the viewpoint of increasing the productivity of foamed particles, it is preferable to perform the impregnation of resin particles with a foaming agent and the foaming of resin particles containing the foaming agent as a series of processes using a single sealed container, as described above.
[0038] In this invention, carbon dioxide is used as the blowing agent. Other blowing agents other than carbon dioxide may be used in combination, as long as they do not hinder the purpose and effects of this invention. Examples of other blowing agents include the following inorganic and organic physical blowing agents. Examples of the inorganic physical blowing agent include air, nitrogen, argon, helium, oxygen, and neon. Examples of the organic physical blowing agent include aliphatic hydrocarbons such as propane, n-butane, isobutane, n-pentane, isopentane, and n-hexane; alicyclic hydrocarbons such as cyclohexane and cyclopentane; halogenated hydrocarbons such as ethyl chloride, 2,3,3,3-tetrafluoropropene, trans-1,3,3,3-tetrafluoropropene, and trans-1-chloro-3,3,3-trifluoropropene; and dialkyl ethers such as dimethyl ether, diethyl ether, and methyl ethyl ether. The blowing agents described above can be used individually or in combination of two or more types. The amount of foaming agent added is determined considering the desired apparent density of the foamed particles, the type of resin used, the type of foaming agent, etc., but the amount of carbon dioxide added is preferably 0.1 parts by mass or more and 30 parts by mass or less, and more preferably 0.5 parts by mass or more and 15 parts by mass or less, per 100 parts by mass of resin particles.
[0039] Furthermore, the foamed particles obtained as described above can be further foamed in multiple stages to produce foamed particles with a higher foaming ratio. For example, by pressurizing the obtained foamed particles with air or the like to increase the pressure inside the bubbles of the foamed particles, and then heating them with steam or the like to further foam them, a two-stage foaming process can be performed to produce foamed particles with a higher foaming ratio.
[0040] The foamed particles produced by the manufacturing method of the present invention may be single-layer foamed particles having only a particulate foamed layer, or they may be multi-layer foamed particles. Examples of multi-layer foamed particles include multi-layer foamed particles comprising a core layer made of a foamed layer and a fusion layer covering at least a part of the surface of the core layer. The fusion layer is a layer for improving the fusion properties between foamed particles during in-mold molding, and may be present on the entire surface of the foamed particles or on only a part of the surface. The fusion layer may be a foamed layer or a non-foamed layer. Examples of resins constituting the fusion layer include polyolefin resins. The melting point or softening point of the resin constituting the fusion layer should be adjusted to be lower than the melting point of the resin constituting the core layer. The method for forming a fusion layer on the surface of foamed particles is not particularly limited. For example, a method of foaming resin particles having a fusion layer on their surface, or a method of obtaining single-layer foamed particles and then attaching a fusion layer to the surface of the foamed particles can be cited. When obtaining foamed particles by foaming resin particles having a fusion layer on their surface, it is preferable to use an extruder capable of co-extrusion to co-extrude a molten mixture for forming the core layer and a molten mixture for forming the fusion layer when manufacturing the resin particles, thereby providing a fusion layer on the surface of the resin particles. Furthermore, when manufacturing multilayer foamed particles in the manufacturing method of the present invention, it is preferable that the core layer has the same configuration as the foamed particles described herein.
[0041] From the viewpoint of adjusting the foamed particles of the present invention to a good crystalline state, it is preferable that in the DSC curve obtained by differential scanning calorimetry of heat flux, in accordance with JIS K7121-1987, where the foamed particles are heated from 23°C to a temperature 30°C higher than the end of the melting peak at a heating rate of 10°C / min, a melting peak (high-temperature peak) appears that has a peak temperature higher than the peak temperature of the main melting peak (intrinsic peak) of the foamed particles. In this case, the DSC curve refers to the DSC curve obtained by heating the foamed particles using the measurement method described above (the DSC curve for the first heating). Furthermore, the main melting peak (intrinsic peak) of the foamed particles refers to the peak that arises from the melting of the intrinsic crystals of the base resin constituting the foamed particles. It should be noted that the intrinsic peak is considered to be a peak that appears due to the melting of the crystals normally present in the base resin constituting the foamed particles. On the other hand, a melting peak (high-temperature peak) with its peak temperature on the high-temperature side of the intrinsic peak is a peak located at a higher temperature than the intrinsic peak that can be confirmed in the first DSC curve. When this high-temperature peak appears, it is presumed that secondary crystals different from the crystals normally present in the base resin constituting the foam particles are present. The DSC curve obtained when the foam particles are heated at a heating rate of 10°C / min from 23°C to a temperature 30°C higher than the end of the melting peak (first heating), then cooled at a cooling rate of 10°C / min from a temperature 30°C higher than the end of the melting peak to 23°C, and then heated again at a heating rate of 10°C / min from 23°C to a temperature 30°C higher than the end of the melting peak (second heating) is called the DSC curve for the second heating. In the DSC curve for the second heating, only the intrinsic peak due to the melting of the crystals normally present in the base resin constituting the foam particles appears. Since this intrinsic peak appears in both the DSC curve for the first heating and the DSC curve for the second heating, it is possible to determine which peak is the intrinsic peak and which is the high-temperature peak by comparing the shape of the DSC curves for the first and second heating and their respective peak positions. From the viewpoint of obtaining a foamed particle molded article having an excellent balance of cushioning properties and rigidity using foamed particles, the heat of fusion of the high-temperature peak is preferably 10 J / g or more and 50 J / g or less, more preferably 11 J / g or more and 30 J / g or less, and still more preferably 13 J / g or more and 20 J / g or less.
[0042] [Apparent Density of Foamed Particles] The production method of the present invention can produce polyolefin-based resin foamed particles that exhibit a lower apparent density, compared to the case where only talc is used as the member used for cell regulation. The apparent density of the foamed particles produced by the production method of the present invention is lower than the apparent density of comparative foamed particles produced in the same manner except that ammonium nitrate was not used, and from the viewpoint of exhibiting excellent light weight, it is preferably 110 kg / m 3 or less, more preferably 100 kg / m 3 or less, still more preferably 90 kg / m 3 or less, even more preferably 85 kg / m 3 or less, and particularly preferably 80 kg / m 3 or less. The lower limit of the apparent density of the foamed particles produced by the production method of the present invention is not particularly limited, but from the viewpoint of more easily suppressing the generation of excessive bubbles, it is preferably 10 kg / m 3 or more, more preferably 30 kg / m 3 or more, still more preferably 50 kg / m 3 or more, even more preferably 65 kg / m 3 or more, and particularly preferably 70 kg / m 3 or more. In other words, the foamed particles produced by the production method of the present invention preferably have an apparent density of 10 kg / m 3 or more and 110 kg / m 3 or less, and more preferably 10 kg / m 3 or more and 100 kg / m 3 or less, and still more preferably 30 kg / m 3 or more and 90 kg / m 3It is even more preferable that the following conditions apply: 50 kg / m 3 More than 85kg / m 3 The following is particularly preferable:
[0043] The manufacturing method of the present invention makes it possible to produce polyolefin resin foam particles exhibiting the desired apparent density range described above by using the polyolefin resin particles described above. For example, the manufacturing method of the present invention produces polyolefin resin foam particles with an apparent density of 10 kg / m³. 3 More than 100kg / m 3 It is possible to provide polyolefin-based resin foam particles as described below.
[0044] The apparent density of foamed particles can be determined by the following measurement method. First, prepare a graduated cylinder filled with water at 23°C. Then, using a tool such as a wire mesh, submerge approximately 500 ml of polyolefin resin foam particles (mass W1), which have been left for two days under conditions of 50% relative humidity, 23°C, and 1 atm, into the graduated cylinder. Then, taking into account the volume of the wire mesh or other tool, measure the volume V1 (cm³) of the polyolefin resin foam particles, which can be read from the rise in water level. 3 By measuring the volume (W1 / V1) of the polyolefin resin foam particles placed in a graduated cylinder, the apparent density of the polyolefin resin foam particles can be determined.
[0045] <Polyolefin-based foamed particles> Next, the polyolefin resin foam particles of the present invention will be described. In the following description, the polyolefin resin foam particles of the present invention may be referred to as the foam particles of the present invention. The manufacturing method of the present invention described above is an example of a preferred manufacturing method of the foam particles of the present invention, but it does not limit the manufacturing method of the foam particles of the present invention. The foamed particles of the present invention are obtained by foaming polyolefin resin particles as described in the manufacturing method of the present invention. Therefore, descriptions of the resin, base resin, talc, ammonium nitrate, and other additives constituting the foamed particles of the present invention should be appropriately referenced from the description of the manufacturing method of the present invention described above.
[0046] The foamed particles of the present invention are polyolefin resin foamed particles with a polyolefin resin as the base resin, and the foamed particles contain ammonium nitrate and talc. The content of ammonium nitrate in the foamed particles of the present invention is preferably 0.02 parts by mass or more and 0.6 parts by mass or less, more preferably 0.03 parts by mass or more and 0.5 parts by mass or less, even more preferably 0.04 parts by mass or more and 0.4 parts by mass or less, and particularly preferably 0.05 parts by mass or more and 0.3 parts by mass or less, per 100 parts by mass of the resin constituting the polyolefin resin foamed particles. In other words, the content of ammonium nitrate in the foamed particles is preferably 0.02 parts by mass or more, more preferably 0.03 parts by mass or more, even more preferably 0.04 parts by mass or more, and particularly preferably 0.05 parts by mass or more, based on 100 parts by mass of the resin constituting the polyolefin resin foamed particles. Furthermore, the content of ammonium nitrate in the foamed particles is preferably 0.6 parts by mass or less, more preferably 0.5 parts by mass or less, even more preferably 0.4 parts by mass or less, and particularly preferably 0.3 parts by mass or less, based on 100 parts by mass of the resin constituting the polyolefin resin foamed particles. The foamed particles of the present invention, having the above configuration, have a higher foaming ratio and suppress the formation of excess bubbles compared to comparison foamed particles having a similar composition except for the absence of ammonium nitrate. Therefore, when the foamed particles of the present invention are subjected to in-mold molding, a foamed particle molded article with excellent lightness and appearance can be provided. Because the formation of excess bubbles is suppressed in the foamed particles of the present invention, relatively uniform secondary foaming occurs when molded in a mold, making it less likely for wrinkles and irregularities to form on the outer surface of the foamed particle molded article. Furthermore, the pressure range over which the foamed particles can be molded is wide, making it easy to obtain a foamed particle molded article with excellent appearance.
[0047] The talc content in the foamed particles of the present invention is preferably 0.01 parts by mass or more and 0.5 parts by mass or less per 100 parts by mass of the resin constituting the polyolefin-based foamed particles, more preferably 0.05 parts by mass or more and 0.4 parts by mass or less, and even more preferably 0.07 parts by mass or more and 0.3 parts by mass or less. In other words, the talc content in the foamed particles is preferably 0.01 parts by mass or more, more preferably 0.05 parts by mass or more, and even more preferably 0.07 parts by mass or more, per 100 parts by mass of the resin constituting the polyolefin resin foamed particles. Furthermore, the talc content in the foamed particles is preferably 0.5 parts by mass or less, more preferably 0.4 parts by mass or less, and even more preferably 0.3 parts by mass or less, per 100 parts by mass of the resin constituting the polyolefin resin foamed particles.
[0048] The ratio of the ammonium nitrate content to the talc content is preferably adjusted to a mass ratio of 0.2 to 6, more preferably to 0.3 to 5, even more preferably to 0.4 to 4, and particularly preferably to 0.5 to 3. In other words, the mass ratio is preferably 0.2 or higher, more preferably 0.3 or higher, even more preferably 0.4 or higher, and particularly preferably 0.5 or higher. Furthermore, the mass ratio is preferably 6 or lower, more preferably 5 or lower, even more preferably 4 or lower, and particularly preferably 3 or lower.
[0049] When the ratio of ammonium nitrate content to talc content is 0.2 or higher by mass, it is easy to achieve a moderately low apparent density, and when the ratio is 6 or lower, it is easy to moderately lower the apparent density while suppressing the formation of excessive bubbles. The reason for this is not clear, but it is thought to be due to the interaction between talc, which functions as a bubble nucleating agent, and ammonium nitrate. Furthermore, when the ratio of the amount of ammonium nitrate added to the amount of talc added satisfies the above range, the pressure range in which the foamed particles can be molded is wide, and a foamed particle molded body with excellent appearance can be easily obtained.
[0050] Furthermore, the talc content and ammonium nitrate content in the foamed particles can be appropriately calculated from the materials used to manufacture the resin particles used to produce the foamed particles. Alternatively, the talc content and ammonium nitrate content in the foamed particles may be directly measured using conventionally known methods.
[0051] [Average bubble diameter] The average bubble diameter of the foamed particles of the present invention is in the range of 20 μm to 250 μm, exhibiting an appropriate bubble diameter while suppressing significant variation in bubble diameter or the inclusion of extremely large bubbles. When foamed particles in which the average bubble diameter is within a specific range and the inclusion of extremely large bubbles is suppressed are used, the pressure range in which the foamed particles can be molded during in-mold molding is wide, and a foamed particle molded article with excellent appearance can be easily obtained. From the viewpoint of easily obtaining a foamed particle molded article with excellent appearance, the average bubble diameter of the foamed particles of the present invention is preferably 40 μm to 180 μm, and more preferably 60 μm to 160 μm. In other words, the average bubble diameter of the foamed particles of the present invention is 20 μm or more, preferably 40 μm or more, and more preferably 60 μm or more. Furthermore, the average bubble diameter is 250 μm or less, preferably 180 μm or less, and more preferably 160 μm or less.
[0052] The average bubble diameter of the foamed particles is measured as follows: Randomly selected polyolefin resin foam particles are cut in approximately two equal parts, exposing the resulting cut surfaces. A scanning electron microscope is used to take photographs that capture the entire cut surface. The area of each bubble is measured by image analysis of all bubbles observed on the cut surface. For example, a WinROOF2021 manufactured by Mitani Corporation can be used as the image analysis device. For each bubble, the equivalent circle diameter is determined from the Ferret diameter, and the bubble diameter is determined from the equivalent circle diameter. This operation is performed for 50 or more foam particles, and the arithmetic mean of the average bubble diameters of the individual foam particles obtained is taken as the average bubble diameter.
[0053] [Average number of excessive bubbles] The foamed particles of the present invention have suppressed formation of excess bubbles inside. In the foamed particles of the present invention, the number of excess bubbles is preferably 5 or less, more preferably 4 or less, even more preferably 3 or less, and particularly preferably 0. An excess bubble in foamed particles refers to a bubble that occupies 5% or more of the area of the cut surface formed by cutting the foamed particle in approximately two equal parts. If the average number of excess bubbles is 5 or less, it can be determined that the formation of excess bubbles has been effectively suppressed.
[0054] The average number of superbubbles can be determined as follows: First, randomly selected foam particles are cut in approximately two equal parts, and the area of the resulting cut surface is measured. Then, bubbles with an area of 5% or more of the cut surface area are counted. This operation is performed for 20 foam particles, and the arithmetic mean of the number of superbubbles for each individual foam particle is taken to determine the average number of superbubbles.
[0055] [Closed cell ratio] Furthermore, the closed-cell ratio of the foamed particles used in the present invention is preferably 80% or more. When the closed-cell ratio is within the above range, the foamed particles exhibit excellent secondary foaming properties, resulting in a wide range of moldable pressures and making it easier to obtain foamed particle molded articles with excellent appearance. From this viewpoint, the closed-cell ratio of the foamed particles is more preferably 85% or more, and even more preferably 90% or more. The percentage of closed cells in foamed particles can be measured as follows: First, the foamed particles are left to cure for 10 days in a constant temperature room under atmospheric pressure, relative humidity of 50%, and temperature of 23°C. Next, in the same constant temperature room, a volume of approximately 20 cm³ is measured. 3 The cured foam particles are used as measurement samples, and their apparent volume Va is accurately measured by the immersion method as described below. After thoroughly drying the measurement samples from which the apparent volume Va has been measured, the true volume Vx of the measurement samples is measured according to procedure C described in ASTM-D2856-70, for example, using a Toshiba Beckmann 930 air-comparative hydrometer. Based on these volumes Va and Vx, the closed-cell ratio is calculated using the following formula (1), and the closed-cell ratio of the foam particles can be determined from the average value of N=5 or more. [Formula 1] Closed cell ratio = (Vx-W / ρ)×100 / (Va-W / ρ) (1) However, Vx in formula (1) above (unit: cm) 3 ) is the true volume of the foamed particle (i.e., the sum of the volume of the resin constituting the foamed particle and the total volume of the closed-cell portion of the foamed particle), and Va (unit: cm) 3 ) is the apparent volume of the foaming particle (i.e., the volume measured from the rise in the liquid level when the foaming particle is submerged in a graduated cylinder of water), W (unit: g) is the mass of the sample used for measurement, and ρ (unit: g / cm³) is the apparent volume of the foaming particle (i.e., the volume measured from the rise in the liquid level when the foaming particle is submerged in a graduated cylinder of water), W (unit: g / cm³) is the apparent volume of the foaming particle (i.e., the volume measured from the rise in the liquid level when the foaming particle is submerged in a graduated cylinder of water), ρ (unit: g / cm³) is the apparent volume of the foaming particle (i.e., the volume measured from the rise in the liquid level when the foaming particle is submerged in a graduated cylinder of water), W (unit: g) is the mass of the sample used for measurement, and ρ (unit: g / cm³) is the apparent volume of the foaming particle (i. 3 ) is the density of the polyolefin resin that constitutes the foamed particles. The density of the polyolefin resin referred to here is the density of the base resin that constitutes the foamed particles being measured.
[0056] [Apparent Density] The apparent density of the foamed particles of the present invention is 110 kg / m³. 3 Preferably, it is 100 kg / m 3 It is more preferable that the following is true: 90 kg / m 3 It is even more preferable that the following conditions apply: 85 kg / m 3 It is even more preferable that the following conditions are met: 80 kg / m 3 The following is particularly preferable: The lower limit of the apparent density of the foamed particles of the present invention is not particularly limited, but is 10 kg / m³.3 Preferably, it should be 30 kg / m 3 It is more preferable that it be 50 kg / m 3 It is even more preferable that the above conditions are met. In other words, the foamed particles of the present invention have an apparent density of 10 kg / m³. 3 More than 110kg / m 3 Preferably, it is 10 kg / m 3 More than 100kg / m 3 The following is more preferable: The foamed particles of the present invention produced by the manufacturing method of the present invention tend to exhibit the apparent density within the preferred range described above. Note that the apparent density of the foamed particles of the present invention is appropriately described in the description of foamed particles produced by the manufacturing method of the present invention, so a detailed explanation is omitted here.
[0057] [Standard deviation of bubble diameter] The standard deviation of the bubble diameter of the foamed particles of the present invention is not particularly limited, but from the viewpoint of obtaining foamed particles with a uniform bubble diameter, it is preferably 20% or less, and more preferably 15% or less. The lower limit is not particularly limited, but is generally around 1%. In other words, the bubble diameter of the foamed particles of the present invention produced by the manufacturing method of the present invention tends to fall within the numerical range of the preferred range described above. Furthermore, the method for determining the standard deviation of the bubble diameter of the foamed particles is described in the examples below.
[0058] [Moisture content] The moisture content of the foamed particles of the present invention is not particularly limited, but from the viewpoint of suppressing shrinkage of the foamed particles immediately after foaming, it is preferably 20% or less, more preferably 17% or less, even more preferably 15% or less, and particularly preferably 13% or less. In other words, the foamed particles of the present invention produced by the manufacturing method of the present invention tend to exhibit the above-mentioned preferred range of moisture content. When foamed particles have a low moisture content immediately after foaming, shrinkage of the foamed particles is easily suppressed, and variations in foamed particle weight due to moisture are reduced, making it easier to stably fill a mold with a consistent amount of foamed particles. In addition, foamed particles with low moisture content do not require a drying process, thus improving production efficiency. The moisture content of foamed particles is determined by removing surface moisture from the foamed particles by passing them through a dehydrator immediately after foaming, and then measuring the weight of the foamed particles. The foamed particles are then dried in a constant temperature tester at 40°C for 24 hours, and the weight of the foamed particles after the internal moisture has been removed is measured. The moisture content (%) is calculated by dividing the weight loss due to drying by the weight of the foamed particles before drying and converting it to a percentage.
[0059] [Carbon Black] The foamed particles of the present invention may contain carbon black. The carbon black content in the foamed particles of the present invention is preferably 0.5 parts by mass or more and 5.0 parts by mass or less, more preferably 1 part by mass or more and 4.5 parts by mass or less, and even more preferably 1.5 parts by mass or more and 4.0 parts by mass or less, per 100 parts by mass of the resin constituting the foamed particles of the present invention. In other words, the carbon black content in the foamed particles of the present invention is preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, and even more preferably 1.5 parts by mass or more, per 100 parts by mass of the resin constituting the foamed particles of the present invention. Furthermore, the carbon black content in the foamed particles of the present invention is preferably 5.0 parts by mass or less, more preferably 4.5 parts by mass or less, and even more preferably 4.0 parts by mass or less, per 100 parts by mass of the resin constituting the foamed particles of the present invention. By adjusting within the above range, it is possible to provide a sufficiently black foamed particle molded body while adding an appropriate amount of carbon black.
[0060] The carbon black content in the foamed particles can be appropriately calculated from the materials used to manufacture the resin particles used to produce the foamed particles. Alternatively, the carbon black content in the foamed particles may be directly measured from test pieces cut from the foamed particles. One measurement method is to use a thermogravimetric differential thermal analyzer (TG-DTA). In this case, the foamed particles are first measured according to JIS K7120-1987. Specifically, the weight of the test piece is measured, and the test piece is heated from 40°C to 500°C at a rate of 10°C / min under a nitrogen atmosphere to decompose the resin constituting the test piece. Then, the atmosphere is changed to an air atmosphere and the temperature is raised to 800°C to decompose the carbon black, and the weight difference from 500°C to 800°C can be measured as the carbon black content. As described above, the carbon black content relative to 100 parts by mass of resin constituting the test specimen can be determined using the measured resin content and carbon black content.
[0061] In the foamed particles of the present invention containing carbon black, the ratio of the carbon black content to the ammonium nitrate content is preferably 1 to 50 by mass, and more preferably 10 to 40 by mass. In other words, the ratio of the carbon black content to the ammonium nitrate content is preferably 1 or more by mass, and more preferably 10 or more by mass. Furthermore, the ratio of the carbon black content to the ammonium nitrate content is preferably 50 or less by mass, and more preferably 40 or less by mass. By adjusting the ratio to this range, it is possible to provide polyolefin resin foamed particles that exhibit sufficient blackness while fully solving the problems of the present invention, namely increasing the foaming ratio and suppressing excessive foaming.
[0062] <Polyolefin-based resin foam particle molded product> A polyolefin resin foam particle molded article can be produced by subjecting the foam particles produced by the manufacturing method of the present invention described above, or by subjecting the foam particles of the present invention to in-mold molding. Such a foam particle molded article enjoys the effects of the present invention, is lightweight, and has an excellent appearance. In the following, a polyolefin resin foam particle molded article obtained by subjecting the foam particles produced by the manufacturing method of the present invention, or by subjecting the foam particles of the present invention to in-mold molding, may be referred to as a foam particle molded article relating to the present invention.
[0063] The in-mold molding method can be appropriately selected from known in-mold molding methods using foamed particles. For example, foamed particles are filled into a mold having a cavity corresponding to the shape of the desired foamed particle molded body, and the foamed particles filled in the mold are heated by applying a predetermined molding pressure using a heating medium, such as steam. The molding pressure can be adjusted, for example, in the range of 0.2 MPa(G) or more and 0.5 MPa(G) or less. In this specification, (G) refers to gauge pressure, that is, the pressure value relative to atmospheric pressure. By heating the foamed particles in the cavity in this way, the foamed particles are further foamed and fused to each other. Next, after heating with the heating medium, such as steam, is completed, the pressure in the cavity is released, and cooling of the mold and the molded body inside the mold is started immediately. When it is confirmed that the pressure (surface pressure) generated on the inner surface of the mold has decreased to below a predetermined value, cooling is stopped, and the foamed particle molded body is removed from the mold. The cooling method here is not particularly limited, but water cooling is one example. Through this series of molding steps, a foamed particle molded body corresponding to the shape of the cavity is obtained.
[0064] The foamed particle molded article according to the present invention has excellent lightness and appearance because the foamed particles used in its manufacture have a high foaming ratio and the formation of excessive bubbles is suppressed. The appearance of the foamed particle molded article according to the present invention is evaluated by visual observation, based on the presence or absence of wrinkles and irregularities on the surface of the foamed particle molded article.
[0065] Furthermore, a foam particle molded article according to the present invention, which is molded using foam particles containing carbon black, may exhibit a black color suitable for use as a vehicle component.
[0066] The molded density of the foamed particle molded article according to the present invention is 10 kg / m³. 3 More than 120kg / m 3 Preferably, it is 20 kg / m 3 More than 100kg / m 3 It is more preferable that the following conditions are met: 25 kg / m 3 More than 90kg / m 3 The following is even more preferable: The density of the molded body (kg / m³) 3 ) is calculated by dividing the mass of the foamed particle molded body by the volume calculated based on its dimensions. [Examples]
[0067] The present invention will be described in detail below with reference to examples, but the present invention is not limited thereto. First, the raw materials of the examples and comparative examples will be described. In the examples and comparative examples described below, polypropylene resin was used as the resin constituting the polyolefin resin particles. The ammonium nitrate, which will be described later, has a thermal decomposition temperature of about 200°C. The parts by mass of the raw materials shown in the example table indicate the amount blended relative to 100 parts by mass of the resin used. The parts by mass of carbon black indicates the amount of pure carbon black blended relative to 100 parts by mass of the resin used.
[0068] (Polyolefin resin) Polypropylene resin: Propylene-ethylene random copolymer, melting point 142°C Polyethylene resin: Linear low-density polyethylene, melting point 124°C (bubble nucleating agent) Talc: A mineral whose main component is hydrated magnesium silicate (3MgO·4SiO2·H2O), manufactured by Matsumura Sangyo Co., Ltd., [Product name: High Filler #12], particle size (d50) 7.5 μm Zinc borate: Manufactured by Borax, product name "Fire Break ZB" (Foaming agent) Ammonium nitrate: Manufactured by Kishida Chemical Co., Ltd. Potassium nitrate: Manufactured by Hayashi Pure Chemical Industries, Ltd., Grade 1. Ammonium sulfate: Manufactured by Kishida Chemical Co., Ltd., special grade. (Carbon Black) Carbon black-containing masterbatch: Product name "PP Black Master Batch, BT920F-JSJ" (manufactured by B&Tech Corporation, CB concentration 45% by weight) (Antioxidant) Hindered phenol stabilizer: BASF product, brand name "Irganox 1010" (pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate])
[0069] (Example 1) <Preparation of polyolefin resin particles> A manufacturing apparatus was prepared that included an extruder with an inner diameter of 50 mm and a strand-forming die attached to the downstream side of the extruder. Polyolefin resin and the raw materials shown in Table 1 were supplied to an extruder and melt-kneaded to obtain a molten mixture. In addition, talc and ammonium nitrate were pre-mixed to form a mixture, which was then supplied to the extruder. The molten mixture was introduced into a strand-forming die, and the extrusion temperature was adjusted to 200°C to extrude the strands. The extruded strands were water-cooled and cut with a pelletizer to obtain an average weight of 1 mg per strand. This yielded polyolefin resin particles with added talc and ammonium nitrate. In Example 1, polypropylene resin was used as the polyolefin resin.
[0070] <Preparation of polyolefin resin foam particles> As described above, 1 kg of the obtained polyolefin resin particles was supplied together with 3 L of water, an aqueous medium, into a pressurized, sealed container with a capacity of 5 L. In addition, 0.3 parts by mass of kaolin as an inorganic dispersant and 0.2 parts by mass of a surfactant (product name: Neogen, manufactured by Daiichi Kogyo Seiyaku Co., Ltd., sodium dodecylbenzenesulfonate) (as active ingredients) were added to 100 parts by mass of the polyolefin resin particles into the sealed container. Next, the sealed container was heated at a rate of 5°C / min while being stirred until it reached the foaming temperature. Then, carbon dioxide was injected into the sealed container as a foaming agent, and the pressure was increased to 2.1 MPa(G). This was then maintained at the same temperature and pressure for 15 minutes. This adjusted the crystalline structure of the resulting foam particles so that a high-temperature peak would appear in the DSC curve obtained by differential scanning calorimetry. Subsequently, the contents of the sealed container (polyolefin resin particles and water) were released to atmospheric pressure, resulting in an apparent density of 75 kg / m³. 3 Polyolefin-based resin foam particles were obtained. In the examples and comparative examples, the foaming temperature was appropriately adjusted to foam the resin particles so that they would have the predetermined apparent density shown in the example table. The average bubble diameter and average number of superbubbles of the foamed particles, as described later, were measured using foamed particles that had been conditioned by standing for 24 hours under conditions of 50% relative humidity, 23°C, and 1 atm.
[0071] <Manufacturing of polyolefin-based resin foam particle molded products> The obtained polyolefin resin foam particles were filled into a mold having a molding cavity capable of forming a plate-shaped foam particle mold measuring 250 mm in length, 200 mm in width, and 20 mm in height, and heated using the following heating method. A metal mold was used as the molding die. The heating method involved preheating (exhaust process) by supplying steam to the mold with drain valves on both sides of the mold open. Then, steam was supplied from one side of the mold to heat it, and then from the other side to heat it further. Subsequently, steam was supplied from both sides of the mold to heat it at the lower limit molding pressure shown in the example table. After heating was complete, the pressure was released and water cooling was started immediately, and water cooling was carried out until the pressure generated on the inner surface of the mold by the foaming force of the foamed particle molded body reached 0.04 MPa (G). After water cooling was complete, the foamed particle molded body was removed from the mold, and this was the foamed particle molded body of Example 1. Furthermore, the evaluation of the appearance and uniformity of blackness of the foamed particle molded body, as described later, was performed using foamed particle molded bodies that had been conditioned by standing for 12 hours under conditions of 50% relative humidity, 80°C, and 1 atm after demolding.
[0072] As described above, the polyolefin resin foam particles obtained in Example 1 exhibited a synergistic effect between talc and ammonium nitrate, resulting in a low apparent density and suppressed formation of excessive bubbles.
[0073] (Examples 2-6) As shown in Table 1, polyolefin resin particles, polyolefin resin foam particles, and polyolefin resin foam particle molded articles were produced in the same manner as in Example 1 described above, except that the amount of ammonium nitrate or talc added was changed, and these were designated as Examples 2 to 6. In Examples 2-6, the amount of ammonium nitrate added was within an appropriate range, and a synergistic effect between talc and ammonium nitrate was obtained, similar to Example 1, resulting in foamed particles with low apparent density. In Examples 2-6, a polypropylene resin was used as the polyolefin resin.
[0074] (Example 7) Except for the addition of 2.6 parts by mass of carbon black, polyolefin resin particles, polyolefin resin foam particles, and a molded polyolefin resin foam particle article were produced in the same manner as in Example 1, and this was designated as Example 7. In Example 7, a polypropylene resin was used as the polyolefin resin. Example 7 showed uniform blackness, and, similar to Example 1, a synergistic effect between talc and ammonium nitrate was achieved, resulting in a low apparent density and suppression of excessive bubble generation.
[0075] (Comparative Examples 1 and 2) Polyolefin resin particles, polyolefin resin foam particles, and polyolefin resin foam particle molded articles were produced in the same manner as in Example 1, except that potassium nitrate or ammonium sulfate was used instead of ammonium nitrate. These were designated as Comparative Examples 1 and 2. In both Comparative Examples 1 and 2, the apparent density of the foamed particles was high, and foamed particles with insufficient magnification were obtained. A cross-sectional photograph of the polyolefin resin foamed particles of Comparative Example 2 is shown in Figure 1. From Figure 1, excessive air bubbles formed in the polyolefin resin foamed particles of Comparative Example 2 can be observed. In Comparative Examples 1 and 2, polypropylene resin was used as the polyolefin resin.
[0076] (Comparative Examples 3 and 4) Polyolefin resin particles, polyolefin resin foam particles, and polyolefin resin foam particle molded articles were produced in the same manner as in Example 1, except that ammonium nitrate was not used, and these were designated as Comparative Example 3. Furthermore, polyolefin resin particles, polyolefin resin foam particles, and polyolefin resin foam particle molded articles were produced in the same manner as in Example 1, except that ammonium nitrate was not used and the amount of talc added was changed to the values shown in Table 2. This was designated as Comparative Example 4. Comparative Example 3 yielded polyolefin resin foam particles with a high apparent density and insufficient magnification. By comparing Comparative Example 3 with Example 1, the significance of using an appropriate amount of ammonium nitrate in combination with talc was confirmed. Comparative Example 4 also yielded polyolefin resin foam particles with a high apparent density and insufficient magnification. The results of Comparative Example 4 suggest that improving the apparent density is difficult even by increasing the amount of talc added. In Comparative Examples 3 and 4, polypropylene resin was used as the polyolefin resin.
[0077] (Reference example 1) Except for the changes described in Table 2, which involved using zinc borate instead of talc as a bubble nucleating agent and not using ammonium nitrate, polyolefin resin particles, polyolefin resin foam particles, and molded polyolefin resin foam particle articles were produced in the same manner as in Example 1 described above, and these were designated as Reference Example 1. Reference Example 1 had a low apparent density and zero average number of superbubbles. In Reference Example 1, a polypropylene resin was used as the polyolefin resin.
[0078] (Examples 8 and 9) Except for changing the extrusion temperature during the production of the resin particles to 230°C and adding 0.3 parts by mass of an antioxidant, polyolefin resin particles, polyolefin resin foam particles, and a molded polyolefin resin foam particle article were produced in the same manner as in Example 1, and this was designated as Example 8. Furthermore, except that the extrusion temperature during the production of the resin particles was changed to 230°C, polyolefin resin particles, polyolefin resin foam particles, and a molded polyolefin resin foam particle article were produced in the same manner as in Example 1, and this was designated as Example 9. In Example 8, despite using a higher extrusion temperature than in Example 1, no excess bubbles were observed in the foamed particles, similar to Example 1. This is thought to be because excess bubbles were suppressed during foaming, and no bubbles were observed in the resin particles. The effect of adding an antioxidant was confirmed in Example 8. In Example 9, 0.2 excess bubbles were observed in the foamed particles. This is thought to be due to bubbles contained within the resin particles, even though excess bubbles were suppressed during foaming. In other words, even with a higher extrusion temperature compared to Example 1, foamed particles and molded foamed particle articles suitable for practical use were obtained. In Examples 8 and 9, a polypropylene resin was used as the polyolefin resin.
[0079] (Example 10) Example 10 was produced in the same manner as Example 4, except that the following conditions were changed. Polyolefin resin particles, polyolefin resin foam particles, and polyolefin resin foam particle molded articles were produced. Polyethylene resin was used as the polyolefin resin. 0.1 parts by mass of ammonium nitrate, a foaming agent, was added. • The extrusion temperature during resin particle manufacturing was changed to 220°C. In the preparation of polyolefin resin foam particles, carbon dioxide was injected as a foaming agent into a sealed container, pressurized to 4.0 MPa(G), and held at the same temperature and pressure for 20 minutes. In the production of polyolefin resin foam particle molded articles, the lower limit molding pressure shown in the Examples table was used, and after heating was completed, water cooling was performed until the pressure generated on the inner surface of the mold became 0.02 MPa (G).
[0080] (Comparative Example 5) Comparative Example 5 was produced in the same manner as in Example 10, except that ammonium nitrate was not used, and consisted of polyolefin resin particles, polyolefin resin foamed particles, and a molded polyolefin resin foamed particle article. Comparative Example 5 used carbon dioxide as a blowing agent and talc as a bubble nucleating agent, resulting in a higher apparent density of the foamed particles.
[0081] As described above, the following measurements or evaluations were performed on polyolefin resin particles, polyolefin resin foam particles, and polyolefin resin foam particle molded articles for each example, comparative example, and reference example 1 obtained. The results are shown in Tables 1 and 2.
[0082] <Evaluation of suppression of bubble generation in resin particles> One hundred polyolefin resin particles were randomly selected, each resin particle was divided into approximately two equal parts, and the cross-section was observed using a scanning electron microscope to check for the presence or absence of air bubbles in each resin particle. The particles were then evaluated according to the following criteria. A: No resin particles containing air bubbles were observed among 100 resin particles. B: In a sample of 100 resin particles, one to less than five resin particles containing air bubbles were observed. C: In a sample of 100 resin particles, five or more resin particles containing air bubbles were observed.
[0083] <Apparent density of foamed particles> Apparent density of polyolefin resin foam particles (kg / m³) 3 The following measurement method was used to determine the value. First, a graduated cylinder filled with water at 23°C was prepared. Approximately 500 ml of polyolefin resin foam particles (mass W1), which had been conditioned by standing for 48 hours under conditions of 50% relative humidity, 23°C, and 1 atm, was submerged in the graduated cylinder using a wire mesh. Then, taking into account the volume of the wire mesh, the volume V1 (cm³) of the polyolefin resin foam particles, which could be read from the rise in water level, was calculated. 3 ) is measured, and the mass W1 (g) of the polyolefin resin foam particles placed in the graduated cylinder is measured to determine the volume V1 (cm³). 3 The apparent density of polyolefin resin foam particles was determined by dividing by (W1 / V1).
[0084] <Average bubble diameter of foamed particles> Randomly selected polyolefin resin foam particles were cut in approximately two equal parts, exposing the resulting cross-sections. A scanning electron microscope was then used to photograph the entire cross-section. The area of each bubble observed in the cross-section was measured by image analysis. The image analysis system used was WinROOF2021 manufactured by Mitani Corporation. For each bubble, the equivalent circle diameter was determined from the Ferret diameter, and the bubble diameter was determined from the equivalent circle diameter. This procedure was performed for 50 foam particles, and the arithmetic mean of the average bubble diameters of the individual foam particles was taken as the average bubble diameter.
[0085] <Average number of excess bubbles in foamed particles> Randomly selected polyolefin resin foam particles were cut in approximately two equal parts, exposing the resulting cross-sections. A scanning electron microscope was used to photograph the entire cross-section. The area of each bubble observed in the cross-section was measured by image analysis. The image analysis device used was WinROOF2021 manufactured by Mitani Corporation. For each bubble, the equivalent circle diameter was determined from the Ferret diameter, and the bubble area was calculated from the equivalent circle diameter. Similarly, for the area of the cross-section of the foam particle, the equivalent circle diameter was determined from the Ferret diameter, and the area of the cross-section was calculated from the equivalent circle diameter. Bubbles with an area of 5% or more of the cross-section area were counted. This procedure was performed for 20 foam particles, and the arithmetic mean of the number of oversized bubbles in each individual foam particle was calculated to obtain the average number of oversized bubbles.
[0086] <Percentage of closed cells in foamed particles> The percentage of closed cells in the foamed particles was measured as follows: First, the foamed particles were left to cure for 10 days in a constant temperature room under atmospheric pressure, relative humidity of 50%, and temperature of 23°C. Next, in the same constant temperature room, a volume of approximately 20 cm³ was measured. 3 The cured foamed particles were used as measurement samples, and their apparent volume Va was accurately measured by the immersion method as described below. After thoroughly drying the measurement samples from which the apparent volume Va was measured, the true volume Vx of the measurement samples was measured using a Toshiba Beckmann 930 air-comparative hydrometer, in accordance with procedure C described in ASTM-D2856-70. Based on these volumes Va and Vx, the closed-cell ratio was calculated using equation (1) below, and the average value for N=5 was taken as the closed-cell ratio of the foamed particles. [Formula 2] Closed cell ratio = (Vx-W / ρ)×100 / (Va-W / ρ) (1) However, Vx in formula (1) above (unit: cm) 3 ) is the true volume of the foamed particle (i.e., the sum of the volume of the resin constituting the foamed particle and the total volume of the closed-cell portion of the foamed particle), and Va (unit: cm) 3) is the apparent volume of the foaming particle (i.e., the volume measured from the rise in the liquid level when the foaming particle is submerged in a graduated cylinder of water), W (unit: g) is the mass of the sample used for measurement, and ρ (unit: g / cm³) is the apparent volume of the foaming particle (i.e., the volume measured from the rise in the liquid level when the foaming particle is submerged in a graduated cylinder of water), W (unit: g / cm³) is the apparent volume of the foaming particle (i.e., the volume measured from the rise in the liquid level when the foaming particle is submerged in a graduated cylinder of water), ρ (unit: g / cm³) is the apparent volume of the foaming particle (i.e., the volume measured from the rise in the liquid level when the foaming particle is submerged in a graduated cylinder of water), W (unit: g) is the mass of the sample used for measurement, and ρ (unit: g / cm³) is the apparent volume of the foaming particle (i. 3 ) is the density of the polyolefin resin that constitutes the foamed particles. The density of the polyolefin resin referred to here is the density of the base resin that constitutes the foamed particles being measured.
[0087] <Heat of fusion at high temperature peak of foamed particles> Based on JIS K7122-2024, differential scanning calorimetry (DSC) was used to obtain the first DSC curve measured when a 2 mg foamed particle was heated at a heating rate of 10 °C / min from 23 °C to a temperature 30 °C higher than the end of the melting peak. Then, in the first DSC curve, a straight line was drawn connecting point I, which corresponds to 80°C on the DSC curve, and point II, which corresponds to the melting end temperature of the foamed particles. Point II, which indicates the melting end temperature, is the high-temperature endpoint of the high-temperature peak, and is the intersection point of the high-temperature peak and the baseline on the high-temperature side of the DSC curve. As described above, after drawing a straight line connecting point I and point II, point IV was defined as the intersection of a straight line parallel to the vertical axis of the graph and passing through the maximum point III, which lies between the eigenpeak and the high-temperature peak, with the straight line connecting point I and point II. The area enclosed by the straight line connecting point IV and point II, the straight line connecting point III and point IV, and the DSC curve connecting point III and point II was defined as the area of the high-temperature peak. The value of the heat of fusion (J / g) of the high-temperature peak was calculated from the area of the high-temperature peak obtained as described above.
[0088] <Standard deviation of bubble diameter in foamed particles> As described above, the average bubble diameter of the 20 foamed particles was calculated, and the value obtained by taking the square root of the unbiased variance was taken as the standard deviation.
[0089] <Moisture content of foamed particles> The moisture content of the foamed particles was measured by the following method. After removing surface moisture by passing the foamed particles through a dehydrator immediately after foaming, the weight of the foamed particles was measured. Subsequently, the foamed particles were dried in a constant temperature tester at 40°C for 24 hours, and the weight of the foamed particles from which the internal moisture had been removed was measured. The moisture content (%) was calculated by dividing the weight loss due to drying by the weight of the foamed particles before drying and converting it to a percentage.
[0090] <Evaluation of the appearance of foamed particle molded products> The appearance of the obtained polyolefin resin foam particle molded articles was visually observed and evaluated according to the following criteria. A: No wrinkles or irregularities were observed on the outer surface of the foam particle molded body. B: Almost no wrinkles and / or irregularities were observed on the outer surface of the foamed particle molded body. C: Wrinkles and / or irregularities were scattered on the outer surface of the foamed particle molded body.
[0091] <Evaluation of uniformity of blackness in foamed particle molded products> The uniformity of the blackness of the foam particle molded body obtained in Example 7 was evaluated as follows. Visually, the color unevenness on the surface of the molded body was evaluated using the following 5-point scale, and the color unevenness of the foam particle molded body was evaluated based on the average value of the evaluations of 5 observers according to the following criteria. (5-point rating scale) 5 points: The surface of the molded body exhibits a uniform black color. 4. The surface of the molded body exhibits a generally uniform black color. 3. Slight color unevenness was observed on the surface of the molded product. Two points: Color inconsistencies were observed on the surface of the molded product. 1. Significant color unevenness was observed on the surface of the molded product. (Evaluation of blackness) A: 4 points or more B: 3 points or more but less than 4 points C: 2 points or more but less than 3 points D: Less than 2 points
[0092] <Density of molded foam particle molded body> The mass of the foamed particle molded body was calculated by dividing it by the volume, which is determined based on its dimensions.
[0093] <Moldable pressure range for foam particle molded bodies> The foamed particles obtained in the examples and comparative examples were used for in-mold molding as described below, and evaluated as follows. In the examples and comparative examples using polypropylene resin, in-mold molding was performed to experimentally mold foam particle molded bodies by varying the molding pressure in 0.02 MPa increments between 0.20 MPa(G) and 0.40 MPa(G). In other words, in-mold molding was performed at a total of 11 different molding pressures. The lowest molding pressure confirmed within the moldable range, as described below, is referred to as the lower limit molding pressure. Furthermore, in the examples and comparative examples using polyethylene resin, in-mold molding was performed by experimentally molding foamed particle molded bodies by varying the molding pressure in 0.02 MPa increments between 0.08 MPa(G) and 0.20 MPa(G). In other words, in-mold molding was performed at a total of seven different molding pressures. As described above, the foam particle molded bodies obtained by in-mold molding were judged to meet the following three criteria (fusion properties, appearance, and recovery properties). Foam particle molded bodies that met all criteria were considered acceptable products, and the moldable pressure range in which such acceptable products could be obtained was evaluated according to the following criteria (moldable pressure range). Note that MPa(G) indicates gauge pressure. In-moldability was evaluated by examining the moldable pressure range. A wider range from the lower limit to the upper limit of the moldable pressure indicates a wider moldable range and is therefore more desirable.
[0094] (Fusibility) The fusion properties of the foam particle molded body were evaluated by the following method. The plate-shaped foam particle molded body was bent and fractured, and the number of foam particles present on the fracture surface (C1) and the number of foam particles that were destroyed (C2) on the fracture surface were determined. The ratio of the number of destroyed foam particles (C2) to the number of foam particles (C1) (C2 / C1 × 100) was calculated as the material destruction rate, and a value of 80% or higher was considered acceptable. (exterior) A 100mm x 100mm rectangle was drawn near the center of a 250mm x 200mm surface of a foam particle molded body. Lines were drawn diagonally from the corners of this rectangle, and the number of voids with a minor axis of 1mm or more and a major axis of 1mm or more along these lines was counted. If the number of voids was less than 5, the product was deemed to have a good appearance and passed the test. Specifically, voids refer to the gaps between foam particles. (Recoverability) The foam particle molded body was left standing for 24 hours in an environment of 23°C and 50% relative humidity. After that, the surface of the foam particle molded body was observed to check for the presence or absence of wrinkles. In addition, the thickness of the central part of the main surface (i.e., the surface with the largest area) and the four corners of the main surface of the flat molded body were measured, and the ratio of the thickness of the central part to the thickness of the thickest part of the four corners was calculated. A product was considered acceptable if no wrinkles were observed at all or very few, and the ratio was 95% or more.
[0095] (Moldable pressure range) A: There are three or more molding pressures that allow for the formation of a satisfactory product. B: There are two molding pressures that allow for the formation of a satisfactory product. C: There is one molding pressure point at which a satisfactory product can be formed. D: No acceptable products could be molded at any of the molding pressures.
[0096] [Table 1]
[0097] [Table 2]
[0098] The above embodiment encompasses the following technical concepts. (1) A method for producing foamed polyolefin resin particles, comprising releasing polyolefin resin particles containing carbon dioxide, which are dispersed in an aqueous medium inside a sealed container, from the sealed container to a pressure lower than the pressure inside the sealed container, thereby foaming the polyolefin resin particles, The aforementioned polyolefin resin particles contain ammonium nitrate and talc. A method for producing foamed polyolefin resin particles, characterized by the above. (2) The method for producing polyolefin resin foam particles according to (1), wherein the amount of talc added is 0.01 parts by mass or more and 0.5 parts by mass or less per 100 parts by mass of the resin constituting the polyolefin resin particles. (3) A method for producing polyolefin resin foam particles according to (1) or (2) above, wherein the ratio of the amount of ammonium nitrate added to the amount of talc added is 0.3 or more and 5 or less by mass ratio. (4) A method for producing polyolefin resin foam particles according to any one of (1) to (3) above, wherein the sum of the amount of talc added and the amount of ammonium nitrate added is 0.04 parts by mass or more and 0.5 parts by mass or less per 100 parts by mass of the resin constituting the polyolefin resin particles. (5) The apparent density of the foamed particles is 10 kg / m³ 3 More than 100kg / m 3 A method for producing polyolefin resin foam particles as described in any one of the above items (1) to (4). (6) A method for producing polyolefin resin foam particles according to any one of (1) to (5) above, wherein the polyolefin resin particles contain carbon black, and the amount of carbon black added is 0.5 parts by mass or more and 5 parts by mass or less per 100 parts by mass of the resin constituting the polyolefin resin particles. (7) A method for producing polyolefin resin foam particles according to (6) above, wherein the ratio of the amount of carbon black added to the amount of ammonium nitrate added is 1 or more and 50 or less by mass ratio. (8) Polyolefin resin foam particles, The average bubble diameter of the polyolefin resin foam particles is 20 μm or more and 250 μm or less. Polyolefin resin foam particles characterized by containing ammonium nitrate and talc in the polyolefin resin foam particles. (9) The polyolefin resin foam particle according to (8) above, wherein the talc content is 0.01 parts by mass or more and 0.5 parts by mass or less per 100 parts by mass of the resin constituting the polyolefin resin foam particle. (10) The apparent density of the polyolefin resin foam particles is 10 kg / m³ 3 More than 100kg / m 3 Polyolefin resin foam particles as described in (8) or (9) above, which are as follows: (11) Polyolefin resin foam particles according to any one of (8) to (10), wherein the ratio of the ammonium nitrate content to the talc content is 0.3 or more and 5 or less by mass ratio. (12) Polyolefin resin foam particles according to any one of (8) to (11), wherein the sum of the talc content and the ammonium nitrate content is 0.04 parts by mass or more and 0.5 parts by mass or less per 100 parts by mass of the resin constituting the polyolefin resin foam particles. (13) The polyolefin resin foam particles according to any one of (8) to (12), wherein the polyolefin resin foam particles contain carbon black, and the carbon black content is 0.5 parts by mass or more and 5 parts by mass or less per 100 parts by mass of the resin constituting the polyolefin resin foam particles. (14) Polyolefin resin foam particles according to (13), wherein the ratio of the carbon black content to the ammonium nitrate content is 1 to 50 by mass.
Claims
1. A method for producing foamed polyolefin resin particles, comprising releasing polyolefin resin particles containing carbon dioxide, which are dispersed in an aqueous medium within a sealed container, from the sealed container to a pressure lower than the pressure inside the sealed container, thereby foaming the polyolefin resin particles, A method for producing polyolefin resin foam particles, characterized in that the polyolefin resin particles contain ammonium nitrate and talc.
2. The method for producing polyolefin resin foam particles according to claim 1, wherein the amount of talc added is 0.01 parts by mass or more and 0.5 parts by mass or less per 100 parts by mass of the resin constituting the polyolefin resin particles.
3. A method for producing polyolefin resin foam particles according to claim 1 or 2, wherein the ratio of the amount of ammonium nitrate added to the amount of talc added is 0.3 or more and 5 or less by mass ratio.
4. A method for producing polyolefin resin foam particles according to claim 1 or 2, wherein the sum of the amount of talc added and the amount of ammonium nitrate added is 0.04 parts by mass or more and 0.5 parts by mass or less per 100 parts by mass of the resin constituting the polyolefin resin particles.
5. The apparent density of the foamed particles is 10 kg / m³. 3 More than 100kg / m 3 A method for producing polyolefin-based resin foam particles according to claim 1 or 2, which is as follows:
6. A method for producing polyolefin resin foam particles according to claim 1 or 2, wherein the polyolefin resin particles contain carbon black, and the amount of carbon black added is 0.5 parts by mass or more and 5 parts by mass or less per 100 parts by mass of the resin constituting the polyolefin resin particles.
7. A method for producing polyolefin resin foam particles according to claim 6, wherein the ratio of the amount of carbon black added to the amount of ammonium nitrate added is 1 or more and 50 or less by mass ratio.
8. Polyolefin resin foam particles, The average bubble diameter of the polyolefin resin foam particles is 20 μm or more and 250 μm or less. Polyolefin resin foam particles characterized by containing ammonium nitrate and talc in the polyolefin resin foam particles.
9. The polyolefin resin foam particle according to claim 8, wherein the talc content is 0.01 parts by mass or more and 0.5 parts by mass or less per 100 parts by mass of the resin constituting the polyolefin resin foam particle.
10. The polyolefin resin foam particle according to claim 8 or 9, wherein the sum of the talc content and the ammonium nitrate content is 0.04 parts by mass or more and 0.5 parts by mass or less per 100 parts by mass of the resin constituting the polyolefin resin foam particle.
11. The apparent density of the polyolefin resin foam particles is 10 kg / m³ 3 More than 100kg / m 3 The polyolefin resin foam particles according to claim 8 or 9, which are as follows:
Citation Information
Patent Citations
Method for producing foamed polypropylenic resin particles, foamed particles of polypropylenic resin and in-mold expansion formed articles of polypropylenic resin
JP2009215485A